Rhabdomyolysis due to Multiple Wasp Stings. (16th September 2012) - Ito, K.; Imafuku, S.; Nakayama, J.
Abstract : Wasp sting is a relatively common arthropod assault, but is sometimes fatal because of anaphylaxis. Rhabdomyolysis is a serious condition, with destruction of striated muscles, and can be induced by various causes such as drugs, heart attacks, CRASH syndrome, and viper bites. Mass envenomation by multiple wasp stings can also cause rhabdomyolysis followed by acute renal failure, although it is extremely rare. We herein report a case who had an anaphylaxis-like reaction and rhabdomyolysis due to multiple wasp stings.